The Role of Guidance and Counseling Teachers in Preventing Bullying at SMA Negeri 3 Kupang - Anjelina Pati Wea; Rosa Mustika Bulor (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Bullying remains a significant issue in senior high schools and negatively affects students’ psychological and social development. This study aims to describe the role of Guidance and Counseling (GC) teachers in preventing bullying by synthesizing relevant literature and best practices implemented in various secondary schools. The study employed a library research approach using content analysis and comparative synthesis of national and international journal articles. The findings indicate that GC teachers hold a strategic position through four key functions: preventive, curative, collaborative, and advocative. The preventive function is implemented through information services, classroom guidance, and psychoeducation; the curative function through individual and group counseling; the collaborative function through coordination with multiple stakeholders in the school environment; and the advocative function through strengthening policies and fostering an anti-bullying school culture. These results highlight that a comprehensive GC service model is effective for bullying prevention and can be adapted to the context of SMA Negeri 3 Kupang with appropriate socio-cultural adjustments.